2011
DOI: 10.1163/19426720-01702005
|View full text |Cite
|
Sign up to set email alerts
|

Is There Really a Resource Curse? A Critical Survey of Theory and Evidence

Abstract: This article provides a critical survey of the resource curse-the idea that mineral and fuel abundance generates negative developmental outcomes in less developed countries. In particular, it examines the idea that mineral and fuel abundance generates growth-restricting forms of state intervention, extraordinarily large degrees of rent seeking, and corruption, which are generally argued to be negative in terms of the developmental outcomes they generate. The analysis surveys the Dutch disease, rentier state, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(34 citation statements)
references
References 23 publications
0
32
0
2
Order By: Relevance
“…Regional studies of Indonesia have consistently identified these regions as being the most prosperous by GRDP per capita between 1999 and 2011 (Hill, Resosudarmo, Vidyattama, 2008;Hill and Vidyattama, 2016). Other, sometimes descriptive studies have also noted that Indonesia has avoided a resource curse (Usui (1997), Rosser (2007), di John (2011) and Chandra (2012). These studies argue that Indonesia successfully escaped a Dutch disease during earlier oil price booms in 1973-1985 as a result of using its oil windfalls to strengthen both its agricultural and manufacturing sectors.…”
Section: Discussionmentioning
confidence: 99%
“…Regional studies of Indonesia have consistently identified these regions as being the most prosperous by GRDP per capita between 1999 and 2011 (Hill, Resosudarmo, Vidyattama, 2008;Hill and Vidyattama, 2016). Other, sometimes descriptive studies have also noted that Indonesia has avoided a resource curse (Usui (1997), Rosser (2007), di John (2011) and Chandra (2012). These studies argue that Indonesia successfully escaped a Dutch disease during earlier oil price booms in 1973-1985 as a result of using its oil windfalls to strengthen both its agricultural and manufacturing sectors.…”
Section: Discussionmentioning
confidence: 99%
“…Since the publication of Sachs and Sachs and Warner (1995), the resource curse hypothesis belongs, despite the manifold exorcizing efforts of different authors, to one of the unabated stylized facts of our time and became enshrined in standard economic principles texts (Auty et al 1998;Wright and Czelusta 2002;Vahabi 2017;Davis 1995;Davis and Tilton 2005). There are many different theoretical approaches to explain the resource curse phenomenon (Di John 2011;Mikesell 1997). Most of them can be classified into two groups.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Historically, many of the most advanced countries in the world today appeared to benefit in this way. More recently, however, less developed countries that have such resources do not appear to have developed in the same way (Di John, 2011) and there is empirical evidence to suggest that resource-rich developing countries have lower per capita income (Auty, 2007), "lower growth rates, lower levels of human development, and more inequality and poverty (Bulte, Damania, & Deacon, 2005;Gylfason, 2001;Sachs & Warner, 1995) " (Kolstad, Wiig, & Williams, 2009, p.954). Pegg (2010) highlights "five different dimensions" of the resource curse literature and these can be summarised as:…”
Section: The Business Case For Exploitationmentioning
confidence: 99%